Breast Cancer Detection Using Convoluted Features and Ensemble Machine Learning Algorithm - Umer, Muhammad; Naveed, Mahum; Alrowais, Fadwa; Ishaq, Abid; Hejaili, Abdullah Al; Alsubai, Shtwai; Eshmawi, Ala’ Abdulmajid; Mohamed, Abdullah; Ashraf, Imran (Cancers, 2022)
Breast cancer is a common cause of female mortality in developing countries. Screening and early diagnosis can play an important role in the prevention and treatment of these cancers. This study proposes an ensemble learning-based voting classifier that combines the logistic regression and stochastic gradient descent classifier with deep convoluted features for the accurate detection of cancerous patients. Deep convoluted features are extracted from the microscopic features and fed to the ensemble voting classifier. This idea provides an optimized framework that accurately classifies malignant and benign tumors with improved accuracy. Results obtained using the voting classifier with convoluted features demonstrate that the highest classification accuracy of 100% is achieved. The proposed approach revealed the accuracy enhancement in comparison with the state-of-the-art approaches.